Analysis of Government Policies from the Old Order to the Reform Era Toward Islamic Education - Nurfadhilah, Nurfadhilah; Zalnur, Muhammad; Masyhudi, Fauza (Intiqad: Jurnal Agama dan Pendidikan Islam, 2024)
This research aims to find out the analysis of government policy making during the old order, new order, and reform era towards Islamic education in Indonesia. A policy that is set arises because of problems that require proper handling. The research used is qualitative research with the type oflibrary research. While the data collection techniques used are data reduction methods, data presentation, data verification and for data analysis techniques using qualitative descriptive methods and historical analysis. Based on this research, it was found that the policy of Islamic education during the old order had begun to be implemented but still at the elementary school level. During the new order, the development of Islamic education policy had reached higher education but there were obstacles that made Islamic education unrecognized. Whereas in the reform era, the implementation of Islamic Education policies in Indonesia was more at the stage of refinement of the old order and new order periods. Therefore, it can be analyzed that the Islamic education policy during the old order, new order and reform era showed a development that was adjusted to the times to answer the challenges of modernity that could increase individual potential.